2017
DOI: 10.1104/pp.16.00074
|View full text |Cite
|
Sign up to set email alerts
|

GmILPA1, Encoding an anaphase-promoting complex-like Protein, affects Leaf Petiole Angle

Abstract: Leaf petiole angle (LPA) is an important plant architectural trait that affects canopy coverage, photosynthetic efficiency, and ultimately productivity in many legume crops. However, the genetic basis underlying this trait remains unclear. Here, we report the identification, isolation, and functional characterization of (), a gene encoding an APC8-like protein, which is a subunit of the anaphase-promoting complex/cyclosome in soybean (). A gamma ray-induced deletion of a fragment involving the fourth exon of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 30 publications
3
42
0
Order By: Relevance
“…Progress would be expedited by the establishment of a ‘toolbox’ for tackling ecological questions related to FN. Although some progress has been made in identifying mutants (Kawaguchi, ; Hartati et al ., ; Chen et al ., ; Zhou et al ., ; Gao et al ., ) that lack FN, it is unclear if the mutations underlying these reductions in FN are free from pleiotropic effects. Another approach might involve more systematic comparison studies of large genera such as Trifolium (Harshberger, ), Mimosa (Simon et al ., ), Cassia (Lasseigne, ) and Oxalis (Steckbeck, ; Gadeceau, ) that are adapted to a wide range of ecological milieux, and whose members show considerable diversity in their leaf movement behaviours.…”
Section: Future Directionsmentioning
confidence: 99%
“…Progress would be expedited by the establishment of a ‘toolbox’ for tackling ecological questions related to FN. Although some progress has been made in identifying mutants (Kawaguchi, ; Hartati et al ., ; Chen et al ., ; Zhou et al ., ; Gao et al ., ) that lack FN, it is unclear if the mutations underlying these reductions in FN are free from pleiotropic effects. Another approach might involve more systematic comparison studies of large genera such as Trifolium (Harshberger, ), Mimosa (Simon et al ., ), Cassia (Lasseigne, ) and Oxalis (Steckbeck, ; Gadeceau, ) that are adapted to a wide range of ecological milieux, and whose members show considerable diversity in their leaf movement behaviours.…”
Section: Future Directionsmentioning
confidence: 99%
“…Another major gene, loose plant architecture 1 (LAP1), affects the leaf petiole angle in soybean. In rice, LAP1 contributes to gravitropic responses and regulates both tiller and leaf angles 16,17 . Rice mutants in which the rostrate growth 1 (PROG1) gene is disrupted show more upright growth 18,19 .…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of apc8‐1 showed that APC8 acts as a dual integrator mediating both microRNA‐dependent cyclin B1 transcription and its degradation during postmeiotic male gametophyte development (Zheng et al ., ). More recently, the soybean GmILPA1 gene encoding an APC8‐like protein, has been shown to have a role in the regulation of leaf petiole angle (Gao et al ., ), suggesting multiple functions for APC8.…”
Section: Introductionmentioning
confidence: 99%